Evaluating characteristics of turbulent flames by using IR thermography and PIV; Infrared Physics & Technology; Vol. 92 - Loboda E. L. Egor Leonidovich; Anufriev I. S. Igor Sergeevich; Agafontsev M. V.; Kopyev E. P. Evgeny; Shadrin E. Yu. Evgeny Yurjevich; Reyno V. V.; Vavilov V. P. Vladimir Platonovich; Lucenko A. V. Alexander Valerjevich (2018, 2018)
Title screen